A new method to determine the 2DEG density distribution for passivated AlGaN/AlN/GaN heterostructure field-effect transistors. (January 2018) - Fu, Chen; Lin, Zhaojun; Cui, Peng; Lv, Yuanjie; Zhou, Yang; Dai, Gang; Luan, Chongbiao; Liu, Huan; Cheng, Aijie
Abstract: A new method to determine the two-dimensional electron gas (2DEG) density distribution of the AlGaN/AlN/GaN heterostructure field-effect transistors (HFETs) after the Si3 N4 passivation process has been presented. Detailed device characteristics were investigated and better transport properties have been observed for the passivated devices. The strain variation and the influence of the surface trapping states were analyzed. By using the polarization Coulomb field (PCF) scattering theory, the 2DEG density after passivation was both quantitively and qualitatively determined, which has been increased by 45% under the access regions and decreased by 2% under the gate region. Highlights: A new method to determine the 2EDG density distribution of the AlGaN/AlN/GaN HFETs after passivation is presented. The increase in the carrier density under the access regions was partly due to the increase of the tensile strain. The intensification of the PCF scattering after passivation played a major role in these variations.